PERMAINAN FUN MAZE: PENINGKATAN KEMAMPUAN MOTORIK PADA ANAK USIA DINI - Dzulkifli, Dzulkifli; arumsari, andini dwi; Maulidiyah, Ummi Masrufah (MOTORIC, 2024)
FUN MAZE is a learning media in the form of an educational game tool (APE) which aims to help early childhood to train fine motor skills in PAUD students. This study uses an experimental research type. This research was conducted at Puspa Indah PAUD, Pacar Kembang, Surabaya. The subjects in this study were 9 Puspa Indah PAUD students aged 5 years. The results of the study are that after the researchers conducted the trial for 2 times not in a row for 2 days at the same time on the first and second days using the FUN MAZE that the researchers made and the results of the trial showed that the subjects experienced an increase in coordination ability the subject's fine motor skills are improving. Keywords: Educational game tools, motor skills